Association of Helicobacter pylori infection with chemotherapy-induced thrombocytopenia in patients with stage III colon cancer: A pilot study†. (March 2014) - Tanriverdi, Ozgur
<x xml:space="preserve">Abstract</x> In this study, the effects of the pre-treatment presence of Helicobacter pylori (H. pylori) infection on chemotherapy-induced thrombocytopenia (CIT) were investigated in patients with stage III colon cancer (CC). A cohort of 74 patients with early stage CC was analysed through a review of clinical records and personal interviews. Helicobacter pylori infections were diagnosed in these patients prior to chemotherapy. The subjects were divided into two groups according to H. pylori infection status: Group 1, H. pylori-positive and Group 2, H. pylori-negative. In all patients, bone marrow toxicity and other study variables were compared. Helicobacter pylori infections were detected in 31 of the74 CC patients. Helicobacter pylori-infected patients (Group 1) showed significantly higher incidences of CIT than did non-infected patients (Group 2; p = 0.029). Helicobacter pylori infection status correlated significantly with tumour location (r = 0.547; p = 0.043) and the most common location of CC in H. pylori-infected patients was the ascending colon (n = 13, 42%) in comparison to non-infected patients (n = 6, 14%; p = 0.042). The relationship between CIT and H. pylori infection status in CC was determined to be independent from the other study variables (p = 0.037; OR = 3.32, CI 95% = 1.16–9.70). In this study, the small number of patients resulted in an inadequate demonstration of the relationship between H. pylori infection and CIT. Therefore, clinical and molecular studies that include more patients are warranted.